A registry for patients with chronic hypoparathyroidism in Russian adults. Issue 7 (July 2020) - Gronskaia, Sofya; Melnichenko, Galina; Rozhinskaya, Liudmila; Grebennikova, Tatiana; Mamedova, Elizaveta; Pigarova, Ekaterina; Przhialkovskaya, Elena; Dzeranova, Larisa; Dedov, Ivan; Fadeyev, Valentin; Brandi, Maria Luisa; Belaya, Zhanna
Abstract : Hypoparathyroidism and pseudohypoparathyroidism are rare endocrine disorders, characterized by low serum calcium due to inappropriate parathyroid hormone (PTH) levels or resistance to its action. There is little epidemiological information regarding chronic hypoparathyroidism in Russia. This study aims to build a registry database of Russian patients with chronic hypoparathyroidism who were referred for hospital treatment in order to conduct initial analysis of clinical presentations and hospital management. The Italian registry model was taken to be able to integrate our data in the future. Two hundred patients with hypoparathyroidism ( n = 194) and pseudohypoparathyroidism ( n = 6) were enrolled over 2 years (2017–2019). The most frequent cause of hypoparathyroidism was neck surgery (82.5%, mostly females), followed by idiopathic hypoparathyroidism (10%), syndromic forms of genetic hypoparathyroidism (4.5%) and forms of defective PTH action (3%). Calcium supplements and alfacalcidol were prescribed in most cases. However, a minority of patients ( n = 6) needed to receive teriparatide as the only way to maintain calcium levels and to prevent symptoms of hypocalcemia. Consequently, substitution treatment with parathyroid hormone should be available in certain cases of hypoparathyroidism. This database will be useful to estimate the potential requirement for recombinant PTH in Russia and standards for clinical and therapeutic approaches.